2013
DOI: 10.15835/nsb539084
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric and Genetic Variation in Three Populations of Indian Salmon (Polydactylus plebeius)

Abstract: Morphometric character analyses and RAPD was used to discriminate and ratify the status of three populations of Indian salmon, Polydactylus plebeius along the coromandel coast of India. Morphometric analyses showed a clear pattern of differentiation between the stocks and revealed the discreteness of two groups, southern stock (Pazhayar) and northern stock (Cuddalore). The univariate analysis of variance showed significant differences between means of the samples for most morphometric descriptors. A total of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Another study of P. monodon populations from east coast of Indian and Pacific Oceans by Sun et al [9] reported morphological similarities among the populations. A similar report was made by Thirumaraiselvi et al [10] in a morphometric study of three populations of Indian Salmon.…”
Section: Morphological Variation Among T Guineensis Populationssupporting
confidence: 81%
“…Another study of P. monodon populations from east coast of Indian and Pacific Oceans by Sun et al [9] reported morphological similarities among the populations. A similar report was made by Thirumaraiselvi et al [10] in a morphometric study of three populations of Indian Salmon.…”
Section: Morphological Variation Among T Guineensis Populationssupporting
confidence: 81%
“…This result also coincides with previous study revealed by RAPD marker, where Nemipterus nemurus (0.0652 ± 0.0520) showed similar gene diversity than N. cyanomus (0.0354 ± 0.0208) and P. caeruleus (0.0283 ± 0.0197) (Parveen et al, 2011). Thirumaraiselvi et al (2013) reported that the Nei's gene diversity (H) was high (0.0733 ± 0.0648) in Cuddalore Polydactylus plebeius population compared to the Vellar (0.0613 ± 0.0344) and Pazhayar (0.0609 ± 0.0416) populations in India. The similar low level of heterogeneity was found in the previous RAPD analysis in Atlantic coast striped bass populations (Bielawski and Pumo, 1997) and catfish populations in Southern Brazil (Sofia et al, 2008).…”
Section: Dendrogrammentioning
confidence: 99%
“…Population structure assessment studies were carried out in several species like Polynemus plebeius (Indian salmon) (Thirumaraiselvi et al, 2013), Lates calcarifer (Indian seabass), Pecten maximus (great scallop) (Heipel et al, 1998), Lepeophtherius salmonis (copepode) (Todd et al, 1997) and Homarus americanus (American lobster) (Harding et al, 1997) by RAPD markers.…”
Section: Introductionmentioning
confidence: 99%